Analisis Kepuasaan Penggunaan Aplikasi Kasir Majoo di Penajam Paser Utara dengan Metode Technology Acceptance Model - Tangkelangi, Eva Selvin Sura; Utamajaya, Joy Nashar (MEANS (Media Informasi Analisa dan Sistem), 2024)
The rapid advancement of information technology has significantly impacted various aspects of life, including business operations. This study aims to eval_uate user satisfaction with the Majoo cash register application in Penajam Paser Utara using the TAM. Through a survey conducted in 2023, involving 100 respondents who have used Majoo for at least three months, data were collected using a structured questionnaire distributed via Google Forms. Statistical analysis using SPSS revealed high user satisfaction, with PU and PEOU significantly influencing overall satisfaction. The results indicate that both PU and PEOU are critical determinants of user satisfaction, consistent with previous TAM research. These findings provide insights for developers to enhance application features and improve user experience.